Videoconferencing in FKE network : modeling, simulation and performance analysis - 256142 Hazly Amir Abdul Hamid (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1999